Laboratory culture of the seagrass, Halophila ovalis (R.Br.) Hooker f. - Bujang, Japar Sidik; Lim, Lai Huat; Zakaria, Muta Harah; Arshad, Aziz; Ogawa, Hisao (2008)
A small-culture system for growing of Halophila ovalis was developed. Plugs of explants were successfuly grown in the native substrate and under the light regime of -200 lmol m-2 S-l. The culturing of H. ovalis in the laboratory permitted observations on (i) the sustain growth and the development of the population, (ii) the reproductive biology (flowering,and fruiting) and (iii) the pattern of seedling development from seeds to mature plants. Plants increased in density via vegetative propagation and sexual reproduction. Plants produced male, female flowers and fruits. The presence of viable seeds and seedlings demonstrated the successful pollination and sexual reproduction of H. ovalis in culture. The morphology of progressive development of H. ovalis seedlings to juverrile or young plants for H. ovalis in culture is described.